Edible coating with probiotic as a quality factor for minimally processed carrots - Shigematsu, Elke [UNESP]; Dorta, Claudia; Rodrigues, Fábio J.; Cedran, Marina F.; Giannoni, Juliana A.; Oshiiwa, Marie; Mauro, Maria A. [UNESP] (Springer Nature, 2018)
The objectives of this study were to elaborate an edible coating based on sodium alginate with probiotic potential and to evaluate the coating’s performance with respect to microbial viability and the characteristics of safety and freshness of minimally processed carrots stored at 8 ± 2 °C. Carrot slices were submerged in a sodium alginate solution with and without the addition of Lactobacillus acidophilus La-14 (7.36 log CFU/g), and gelling was activated by subsequent immersion in a calcium chloride solution. Physical, chemical and microbiological analyses of coated and non-coated samples were performed over a period of 19 days. At the end of this period, the viable cell count of the probiotic remained at 7.11 log CFU/g. Thus, the alginate coating was an efficient support for L. acidophilus. In addition, comparing the acidity increase between the treatments, samples with probiotic coating presented the lowest statistically significant variation, suggesting that the probiotics had reduced the metabolism of the minimally processed carrot slices. The barrier created by the coatings also contributed to the quality of the minimally processed carrots by conserving their moisture and minimizing color changes during storage. These factors are important determinants of the successful commercialization of these products.
Keywords: Fresh-cut vegetables; Lactobacillus acidophilus; Sodium alginate; Viability